OCEANOGRAPHY OF THE BLACK SEA: A REVIEW OF SOME RECENT RESULTS - Özsoy E.; Ünlüata Ü. (My University, 1997)
A new synthesis of the Black Sea oceanography is presented, primarily based on studies carried out in the southern Black Sea, as well as on some recent work covering the entire basin, obtained in a new era of increasing cooperation between the riparian countries. A review of the physical environment is given. Seasonal and interannual climatic variability of the system are discussed in relation to its hydrology. Water mass variability and formation are studied, with emphasis on the inflow of Mediterranean waters, pycnocline variability, shelf and internal mixing, and double diffusive convection. The general circulation of the basin, and the roles of stratification, topography and coastline variations in determining the behaviour of the rapid, unstable boundary currents and upwelling along the coast are discussed, based on hydrographic data and satellite observations. Impacts of the physical processes on the ecosystem are discussed.